2009
DOI: 10.1111/j.1365-2672.2008.04104.x
|View full text |Cite
|
Sign up to set email alerts
|

Comparative analysis of different TaqMan real-time RT-PCR assays for the detection of swine Hepatitis E virus and integration of Feline calicivirus as internal control

Abstract: Aims:  The aim of this study was to compare the performance of four TaqMan RT‐PCR assays with a commonly used nested RT‐PCR and to include the Feline calicivirus (FCV) as an internal control. Methods and Results:  RNA extracted from 87 swine faecal samples and 103 swine blood samples was subjected to different detection systems. Faecal samples naturally contaminated with Hepatitis E virus (HEV) and negative samples were artificially inoculated with 3·2 × 103 PFU of FCV. Detection results obtained on faecal and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
55
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(58 citation statements)
references
References 43 publications
(137 reference statements)
3
55
0
Order By: Relevance
“…The RT-PCR based on ORF2 rarely detected the 100-fold-diluted genotype 3c and 3e samples, and our assays of several clinical plasma samples showed that the RT-PCR based on ORF2 significantly underestimated the HEV RNA concentration in genotype 3c samples compared to the genotype 3f samples. These data agree well with findings described previously by Ward et al (46), who studied the performances of 4 real-time RT-PCRs based on ORF3 and ORF2 by testing Canadian swine genotype 3 samples. Those authors compared the threshold cycle (C T ) values obtained with the real-time RT-PCR tests and found that the RT-PCR test based on ORF3 was the most sensitive test for the detection of swine HEV strains (46).…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…The RT-PCR based on ORF2 rarely detected the 100-fold-diluted genotype 3c and 3e samples, and our assays of several clinical plasma samples showed that the RT-PCR based on ORF2 significantly underestimated the HEV RNA concentration in genotype 3c samples compared to the genotype 3f samples. These data agree well with findings described previously by Ward et al (46), who studied the performances of 4 real-time RT-PCRs based on ORF3 and ORF2 by testing Canadian swine genotype 3 samples. Those authors compared the threshold cycle (C T ) values obtained with the real-time RT-PCR tests and found that the RT-PCR test based on ORF3 was the most sensitive test for the detection of swine HEV strains (46).…”
Section: Discussionsupporting
confidence: 83%
“…These data agree well with findings described previously by Ward et al (46), who studied the performances of 4 real-time RT-PCRs based on ORF3 and ORF2 by testing Canadian swine genotype 3 samples. Those authors compared the threshold cycle (C T ) values obtained with the real-time RT-PCR tests and found that the RT-PCR test based on ORF3 was the most sensitive test for the detection of swine HEV strains (46). Unfortunately, those researchers did not determine the HEV subtypes, and their assays were only semiquantitative.…”
Section: Discussionsupporting
confidence: 83%
“…There was no change in the clinical status occurred during the follow-up period (median follow-up time of 33.8 months) in the disease-free group. The comparative C T method used for quantifying the mRNA of onfFN in this study is an acceptable technique (Chang et al, 2002;Ward et al, 2009). The between-run and within-run variations were less than 2%, suggesting reliability of the procedure.…”
Section: Discussionmentioning
confidence: 96%
“…Comparisons of RT-PCR assays have shown a 10-to 1,000-fold variation in sensitivity when samples were tested in parallel in the same laboratory (20,21). In a blinded study to investigate the performance of conventional and real-time RT-PCR assays in 20 laboratories that performed HEV RNA detection on a regular basis, variations in sensitivity on the order of 100-to 1,000-fold were found using a standard panel of HEV genotype 3 and 4 strains (12).…”
mentioning
confidence: 99%